What determinants of COVID-19 vaccine hesitancy among Chinese nursing students? A cross-sectional study - Wang, Xin; Liu, Ming; Li, Yuanzhen; Mei, Xiaoxiao; Liao, Shuting; Liang, Qingqing; Liu, Yachen (Frontiers in Public Health, 2024)
The coronavirus disease 2019 continues to threaten human health, and health professionals, including nursing students, usually work in healthcare frontiers with a high risk of infection. Vaccination is currently one of the most effective preventive measures. This study aimed to explore the determinants of COVID-19 vaccine hesitancy in nursing students.In November 2022, a sample of undergraduate nursing students was recruited from several medical schools in Anhui Province, China, and an online cross-sectional survey was conducted using the questionnaire star platform (Wenjuanxin). A Chi-square test was used to explore vaccine hesitancy among nursing students with different social demographic characteristics and vaccine attitudes.Binary logistic regression analysis was then used to determine the influence factors of vaccine hesitancy among nursing students.